Determinants of Maternal Mortality in Pakistan - Shahida Abbasi; Muhammad Younas (Mashhad University of Medical Sciences, 2015)
Maternal mortality refers to the death of a woman who dies during pregnancy or within six weeks after delivery. A number of factors contribute to the high maternal mortality ratio around the globe, particularly, in underdeveloped countries. Pakistan has the highest mortality ratio (260 per 100,000 live births) in the region and is one of the developing countries which have committed to decrease maternal mortality by 2015, according to the millennium developing goals (MDG) 5. However, there are number of factors which made Pakistan unable to achieve the MDG 5 by 2015. In Pakistan there are many factors such as biological, socio-economic, cultural and poor quality of Reproductive Health Services (RHS), which contribute to the alarming figure of Maternal Mortality.. This paper aimed to do an in-depth analysis of the determinants of maternal mortality in Pakistan.